2007
DOI: 10.1194/jlr.m700033-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

SREBP-1-independent regulation of lipogenic gene expression in adipocytes

Abstract: Sterol regulatory element-binding protein (SREBP)-1c is now well established as a key transcription factor for the regulation of lipogenic enzyme genes such as FAS in hepatocytes. Meanwhile, the mechanisms of lipogenic gene regulation in adipocytes remain unclear. Here, we demonstrate that those in adipocytes are independent of SREBP-1c. In adipocytes, unlike in hepatocytes, the stimulation of SREBP-1c expression by liver X receptor agonist does not accompany lipogenic gene upregulation, although nuclear SREBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 50 publications
4
93
2
Order By: Relevance
“…Previous reports demonstrated that expression of Srebp‐1c and its downstream target genes is upregulated and downregulated under fed and fasting conditions, respectively, in both the liver and WAT (Horton et al ., 1998; Sekiya et al ., 2007). However, we observed that CR enhanced expression of proteins involved in FA biosynthesis, via Srebp‐1c, in WAT, regardless of feeding condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that expression of Srebp‐1c and its downstream target genes is upregulated and downregulated under fed and fasting conditions, respectively, in both the liver and WAT (Horton et al ., 1998; Sekiya et al ., 2007). However, we observed that CR enhanced expression of proteins involved in FA biosynthesis, via Srebp‐1c, in WAT, regardless of feeding condition.…”
Section: Discussionmentioning
confidence: 99%
“…LXR's role in hepatic lipogenesis is very well established; in this tissue, LXR induces lipid accumulation through stimulation of its target genes SREBP1c, fatty acid synthase (FAS), stearoyl-CoA (SCD1), and acyl cocarboxylase 1 (ACC1) ( 48,59 ). In adipose tissue, the story becomes less predictable, since LXR activation in wild-type mice is not accompanied by an increase in adipose tissue FAS, despite the expected increase in SREBP1c ( 60 ). In addition, although the obesity resistant LXR ␣ ␤ Ϫ / Ϫ mice exhibit the expected attenuation of expression of the lipogenic LXR target genes in the liver, in adipose tissue, these same genes are actually increased despite having smaller adipocytes ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It also decreased Glut 4, which is regulated by C/EBPa and FAS. Although SREBP-1c plays a critical role in the induction of FAS in hepatocyte (24), a recent study has revealed that SREBP-1c is not committed to the regulation of lipogenesis in adipocyte (25). TNFa markedly increased cytokines IL-6 and MCP-1, which are directly regulated by NF-jB in the spiral ligament fibrocyte (26).…”
Section: Discussionmentioning
confidence: 99%